STATUS KESEHATAN LANJUT USIA GEREJA RAWAMANGUN JAKARTA TIMUR - Mawi, Martiem; Tandean, Reza; Abikusno, Nugroho (E-Journal Widya Kesehatan dan Lingkungan, 2005)
To determine the health status of older persons living in the community. A cross-sectional observational study was done of 59 older persons of a Catholic church in Rawamangun, east Jakarta, who volunteered in the study through informed consent. Data collected were physical, blood pressure, lipid profile, ECG, VEP1, weight, height knee height and food frequency. Older persons with hypertension (>140/90) were 14 (23.7%). The lipid profile of older persons were 31 (52.5%) subject had hypercholesterolemia (200 mg/L), 5 (8.5%) subject had hypertriglyceridemia (200>mg/L) 13 (22.0%) subjects had hypo-high-density-lipoproteinemia (<45 mg/L), and 12 (20.3%) subjects had hyper-low-density-lipoproteinemia (>150 mg/L). Older persons with abnormal ECG were 16 (27.1%), 2 (3.4%) subjects had less than normal VEP1 and 37 (62.7%) subjects exercised >= 3 times weekly. Body Mass Index of older persons were 12 (20.3%) subjects BMI below 20.27 (45.8%) BMI between 20-25, 18 (30.5%) between 25-30, and 2 (3.3%) subjects BMI above 30(obesity).